Multiply both sides by 2pi:
F(2pi) = sqrt(g/l)
Square both sides:
F^2 (2pi)^2 = g/l
Solve for l by dividing both sides by F^2 (2pi)^2
L = g/ F^2 (2pi)^2
Simplify:
L = g / 4pi^2(f^2)
Answer:
396
Step-by-step explanation:
You multiply 3 times 3 times 4 times 11 to find your answer 396.
Answer:
180
Step-by-step explanation:
1%=3
25%=75
15%=45
100-(25+15)=60
60%=60*3=180
Answer:
h(n+1) = -⅓ h(n), h(0) = 63
Step-by-step explanation:
h(n) = 63 (-⅓)ⁿ
This is a geometric series where the first term is 63 and the common ratio is -⅓.
Therefore, each term is -⅓ of the previous term.
h(n+1) = -⅓ h(n), h(0) = 63.